Prompting visual attention to print versus pictures during shared book reading with digital storybooks for preschoolers with ASD compared to TD peers. Issue 2 (11th October 2021) - Wicks, Rachelle; Westerveld, Marleen; Stainer, Matthew; Paynter, Jessica
Abstract: Prompting children to look at print and picture content during shared book reading (SBR) facilitates joint attention and early language and literacy learning opportunities for typically developing (TD) children. Whether preschoolers with autism spectrum disorder (ASD) respond similarly to bids for joint attention during SBR and how autism characteristics impact upon their responsiveness is currently unclear. This is important given these children are at risk of persistent language and literacy challenges. To address this, we examined the effects of prompts that were solely verbal versus verbal with pointing on visual attention to print and picture targets during SBR with digital storybooks for 34 children with ASD and 27 TD peers. Children with ASD looked as frequently at print targets, but less frequently at picture targets, when prompted compared to TD peers. Both prompt types showed similar effects in shifting children's visual attention to print and picture targets at group level. When groups were combined, autism characteristics influenced children's responsiveness to verbal versus verbal with pointing prompts to print targets, but not to picture targets; children looked more frequently at print targets as autism characteristics increased when verbal prompts were used, with a large effect shown ( d  = 0.91). Overall, findings suggest that prompting children with ASD to look at print and pictures during SBR with digital storybooks may be helpful in facilitating joint attention to storybook content. Implications for the development of effective early interventions aimed at providing emergent literacy support for children with ASD are discussed. Lay Summary: We looked at how prompting impacted upon where children with autism look during shared book reading with digital storybooks compared to children without autism using eye‐tracking. We found the target (pictures or print) was what mattered and number of autism characteristics impacted how responsive children were to different types of prompts. This helps us to understand how prompting may help children with autism to look at print or pictures during shared book reading which could support language or reading interventions.